1999
DOI: 10.1021/ja991130e
|View full text |Cite
|
Sign up to set email alerts
|

A Remarkable Family of Rhodium Acetonitrile Compounds Spanning Three Oxidation States and with Nuclearities Ranging from Mononuclear and Dinuclear to One-Dimensional Chains

Abstract: A series of homoleptic cations of Rh(I,II), Rh(II), and Rh(III) have been synthesized and characterized in the solid-state and in solution. Three new dinuclear compounds of dirhodium(II,II) were prepared by treatment of Rh2(O2CCH3)4(L)2 with Et3OBF4 or Me3Si(CF3SO3) in acetonitrile or propionitrile. The cations in [Rh2 II,II(MeCN)10][BF4]4 (1), [Rh2 II,II(MeCN)10][SO3CF3]4 (2), and [Rh2 II,II(EtCN)10][BF4]4 (3) contain eight equatorial RCN groups oriented in an approximately square planar arrangement around th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
64
0
3

Year Published

2001
2001
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(73 citation statements)
references
References 59 publications
6
64
0
3
Order By: Relevance
“…This tetranuclear structure is basically identical with those of the previously reported ones with other amidate ligands [19][20][21][22]. The X-ray analysis revealed that four PF 6 À ions exist per one tetranuclear unit, and therefore the platinum oxidation states of 2 are +2. with Pt(+2.25) 4 mixed-valence, and the one unpaired electron is delocalized over the four platinum cores.…”
Section: Methodssupporting
confidence: 86%
See 2 more Smart Citations
“…This tetranuclear structure is basically identical with those of the previously reported ones with other amidate ligands [19][20][21][22]. The X-ray analysis revealed that four PF 6 À ions exist per one tetranuclear unit, and therefore the platinum oxidation states of 2 are +2. with Pt(+2.25) 4 mixed-valence, and the one unpaired electron is delocalized over the four platinum cores.…”
Section: Methodssupporting
confidence: 86%
“…Pivalonitrile and sodium hexafluorophosphate were obtained from Tokyo Kasei Industrial Co. Rhodium 6 . The details of the synthetic methods were described in the previous report [18].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…If the unpaired electron were in the π* orbital one might expect g ʈ Ͼ g Ќ . The EPR spectrum of complex 3 is similar to the spectra of the chain compounds [7][8][9] and [Rh 2 (NCMe) 8 ] n -(BF 4 ) 3n [12] but different to that of the discrete dinuclear paramagnetic complex [Rh 2 (µ-OOCCH 3 ) 2 (bpy) 2 (NCCH 3 ) 2 ]-[BF 4 ]. [18] It was suggested that in the latter compound the unpaired electron is delocalized over the bpy ligand.…”
Section: (H 2 O) 2 ]mentioning
confidence: 74%
“…A 2 . In this compound, the Rh-Rh distances are longer (2.8442 and 2.9277 Å), [11,12] which suggests that rhodium MWs containing carboxylato bridging ligands are more stable. This conclusion was confirmed by formation of formato complexes [Rh 4 (µ-OOCH) 4 5+ cores, respectively.…”
Section: (H 2 O) 2 ]mentioning
confidence: 86%